PENGARUH CAR, LDR DAN ROA TERHADAP LABA PERUSAHAAN PERBANKAN TERDAFTAR DI BURSA EFEK INDONESIA - Lasminisih Lasminisih; Emmy Indrayani (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Company financial statement can be used to monitor the performance of a company. Financial statements are also used as a means for decision making, so that the company can anticipate future plans. The purpose of this study was to find out the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Return on Assets (ROA) on profit changes percentage of Banking Companies. The number of sample companies used in this study were 27 Banks listed in the Indonesia Stock Exchange with observation periods from 2007 to 2008. The method used in this study was multiple regression. The results of this study have indicated that CAR, LDR and ROA gave significant effects on changes in Banks profit, so that Banking Companies performances can be measured.